Mathematics and Culture: Affine Transformation Representation of Atakkae Traditional House in Wajo Regency Using Blender Software - Ja’faruddin, Ja’faruddin; Chen, Wen Haw; Oeitama, Whennie Youngger; Padasasih, Andi Ismudiah; Wijayana, Widhi Kesawa; Murnianti, Murnianti; Rahman, Nurul Qalbi; Utami, Indah Tri Wira (Journal of Mathematics, Computations and Statistics, 2025)
This study examines the application of affine transformations to the geometric structure of the Atakkae traditional house in Wajo Regency, South Sulawesi, in the context of ethnomathematics. This traditional house, known as Saoraja La Tenri Bali, is a typical Bugis stilt house with architectural uniqueness in the form of 101 pillars and large dimensions. Affine transformations were used to analyze the geometric elements of this traditional house, including scale, rotation and shear, in order to understand the mathematical relationships in traditional design. This research used a descriptive qualitative approach with data collected through direct observation and literature review. Geometric visualization was conducted using Blender software, which utilizes matrix transformation to model the structure of the traditional house in detail. The results show that the geometric elements in Atakkae traditional houses reflect a combination of local wisdom and mathematical principles, which are relevant in preserving culture while providing new insights into the relationship between mathematics and tradition. The findings are expected to contribute to the documentation of cultural heritage and the development of ethnomathematics learning.